2018
DOI: 10.1038/s41598-018-19698-z
|View full text |Cite
|
Sign up to set email alerts
|

Offline stimulation of human parietal cortex differently affects resting EEG microstates

Abstract: The interference effects of transcranial magnetic stimulation (TMS) on several electroencephalographic (EEG) measures in both temporal and frequency domains have been reported. We tested the hypothesis whether the offline external inhibitory interference, although focal, could result in a global reorganization of the functional brain state, as assessed by EEG microstates. In 16 healthy subjects, we inhibited five parietal areas and used a pseudo stimulation (Sham) at rest. The EEG microstates were extracted be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 49 publications
5
31
0
Order By: Relevance
“…Notably, microstate B, associated with visual sensory processing 34 , 37 but also shown to decrease during hypnosis 47 , was not associated with prosociality, indicating a complex relationship between different kinds of sensory, bottom-up processing and prosociality. Furthermore, we found indications of a negative association of attention-related microstate D 34 , 37 , 48 with prosociality (this correlation was no longer significant after correction for multiple comparisons across microstate classes), tentatively suggesting an antagonistic relationship of specific kinds of top-down compared to bottom-up processing with prosociality which may be corroborated in future research.…”
Section: Discussionsupporting
confidence: 69%
“…Notably, microstate B, associated with visual sensory processing 34 , 37 but also shown to decrease during hypnosis 47 , was not associated with prosociality, indicating a complex relationship between different kinds of sensory, bottom-up processing and prosociality. Furthermore, we found indications of a negative association of attention-related microstate D 34 , 37 , 48 with prosociality (this correlation was no longer significant after correction for multiple comparisons across microstate classes), tentatively suggesting an antagonistic relationship of specific kinds of top-down compared to bottom-up processing with prosociality which may be corroborated in future research.…”
Section: Discussionsupporting
confidence: 69%
“…Compared to other EEG correlates that are local and require a period of a certain minimum duration, the EEG microstates have been proposed as a widespread measure of the temporary human brain activity that does not change continuously but remains quasi-stable for epochs of about 80-120 ms (Lehmann et al, 2005). The topography of the EEG microstates has been deeply investigated at rest (Britz et al, 2010;Croce et al, 2018a), and several studies associated such topographies with other EEG correlates and with BOLD activity. Specifically, Britz et al (2010) reported a link between the BOLD activations in areas belonging specifically to human networks and the four common resting EEG microstate topographies (A, B, C, and D), and more recently, the emergence of these four microstate topographies at rest was linked with intra-cortical alpha oscillations (Milz et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the applied spatio-temporal analysis approach clusters the resting EEG signal into a limited number of scalp electrical potential topographies that remain stable for certain time periods (60–120 ms) before dynamically changing into a different topography that remains stable again (for recent studies taking this approach, see 23,24 ). These time periods of stable topographies are known as “microstates”, and transitions between microstates are believed to represent sequential coordinated activity of various, distributed neural networks 6,7 .…”
Section: Introductionmentioning
confidence: 99%